A novel strategy for exploring food originated anti-adipogenesis substances and mechanism by structural similarity evaluation, ADME prediction, network pharmacology and experimental validation. Issue 15 (22nd June 2021) - Zhang, Feng-xiang; Tang, Zi-ling; Qiu, Zuo-cheng
Abstract : A proposed schematic diagram for the SANE strategy on screening potential functional substances in natural products (food, herb, etc .). Abstract : Screening potential functional substances based on active compounds is still a challenge faced by researchers since hundreds and thousands of possible compounds exist in natural products (food, herb, etc. ). In this study, an integrated strategy by a combination of structural similarity evaluation, ADME (absorption, distribution, metabolism, excretion) prediction, network pharmacology and experimental validation (SANE strategy) was proposed and applied to explore anti-adipogenesis substances. This strategy was divided into four parts: first, potential compounds were screened based on representative active compounds by similarity evaluation and ADME prediction. Second, the activity of targeted compounds was evaluated in vitro based on the molecular biology method. Third, network pharmacology was used to explore potential targets and pathways. Last, the core pharmacological mechanism was confirmed by modern pharmacology methods. As a result, 8-prenylgenistein (8PG) was screened with chemical structure similarity with genistein and improved ADME propriety. Meanwhile, 8PG was found to present significant anti-adipogenesis effects in pre-adipocyte 3T3-L1 cells and primary human bone marrow stromal cells (hBMSC). Through using methods including: chemical staining, functional assays, and Real time PCR, 8PG was found to present more potency than genistein in suppressing the adipocyte differentiation. Further, the potential pharmacological mechanism was predicted, and significant effects of 8PG on activating the Wnt/β-catenin pathway in 3T3-L1 cells and hBMSC were confirmed by  immunoblotting in the absence/presence of signaling pathway blocker and immunofluorescence staining. A new insight for exploring more potent compounds based on accurate effect compounds is provided in our work. Moreover, a potential compound (8PG), suppressing adipogenesis, was also supplied.